PENGARUH HARGA DAN STORE ATMOSPHERE TERHADAP KEPUASAN KONSUMEN DI RESTORAN BAHAGIA SELECTA KOTA BATU - Mochammad Yusuf Amrulloh; Fullchis Nurtjahjani (CV. ADIBA AISHA AMIRA, 2024)
The purpose of this study is to find out and examine whether price affects consumer satisfaction of bahagia restaurant selecta batu city and find out whether store atmosphere affects consumer satisfaction of bahagia restaurant selecta batu city and find out whether price and store atmosphere affect consumer satisfaction of bahagia restaurant selecta batu city. This research is a type of quantitative research, as for the population in this study, namely consumers who have visited Batu City Selecta Restaurant. With a sample of 100 respondents taken using a purposive sampling approach and analyzed using multiple linear regression analysis techniques. The results of partial and simultaneous hypothesis testing show that Price and Store atmosphere have a positive and significant effect on consumer satisfaction of Batu City Selecta Restaurant. This research shows that Store atmosphere is more dominant than Price